Dark Swan; Contemporary Tales of the Gothic Antipodes - Giambazi, Kelsey (Self Published, 2018)
Dark Swan – Contemporary Tales of the Gothic Antipodes, curated by Kelsey Ashe, is a four-week exhibition providing artists and audiences an opportunity to examine an aesthetic of Australian Gothic Romanticism in relation to the real and imagined history, landscape and characters of Western Australia through art, film, costume and performance.